The effects of two-week fungal-based essence in healthy Malaysian adults: a pilot randomized controlled trial - Lee, Ho Shin; Chang, Shu Juin; Emang, Diana; Liu, Juan; Wong, Ling Shing; Ng, Hou Hong; Lee, Shiou Yih (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2025)
Despite many edible fungi being claimed to be potential sources of functional food, clinical trials on the effect of fungal-based essence on cognitive function are generally7 lacking. This study aims to determine the effect of a commercialized fungal-based essence on general health, perceived stress, and fatigue levels, derived from their questionnaire-based perception after the consumption of fungi extract. Methods: This study conducted a randomized, double-blind, placebo-controlled clinical trial on healthy Malaysian adult volunteers using the hot water extraction of five edible fungi species, i.e., Boletus edulis, cordyceps militaris, Ganoderma lucidum, Hericium Erinaceus, and Lentinula edodes. 40 participants were allocated to 3:1 ratio to receive fungal-based essence and chicken essence. The questionnaire was carried out at baseline and on day 14, with data from 40 participants being analysed; while the 10-people control group were given with Chicken Essence. Results:The T-test analysis showed that the ingestion of fungal-based essence improved general health,lowered down perceived stress, and reduced fatigue levels significantly in both the test and control groups. Conclusion: Our findings support the consistent uptake of fungal-based essence could be effective for the improvement of general health, and overcoming stress, as well as a promising candidate for use as an anti-fatigue food.